Pengaruh Berbagai Kombinasi Ketebalan Media Filter Pasir dan Zeolit Terhadap Penurunan Kadar Besi (Fe) dan Mangan (Mn) pada Air Sumur Perum Nilasari Pabelan Kartasura - HANDAYANI, TITIK ISDIANA (2011)
Contents of Fe and Mn on water which have flow standardization capacity which causes environment and healthy problems. Content Fe and Mn in Nilasari Pabelan Kartasura have exceeded capacity standardized are 3,163 mg/l and 1,012 mg/l. degradation of Fe and Mn can be done by sand zeolite filtration. The purposes of this research are to know about some influences of thick sand zeolite filter on degradation of contains of Fe and Mn. The method which used in this research are experiment which test experiments pretest-post with control groups desig. Populations in this research are all of arthesis well in Perum Nilasari RT 01 RW VI. Accounts of sample which used 20 liter, every practically used 5 liter to 3 more repeated. Result of statistics use oneway anova media in 1 rule which SPSS 17. The results of this research show are the influence of thick in sand zeolite media on degradation contains of Fe and Mn. The result of laboratory test show that control of Fe and Mn are 3,157 mg/l and 1,011 mg/ sand- zeolite have thick about 40 cm in contains of Fe and Mn about 0,265 mg/l dan 0,275 mg/l, thick of sand- zeolite 50 cm have contains of Fe and Mn are 0,193 mg/l dan 0,164 mg/l, thick of sand- zeolite 60 have contains of Fe and Mn are 0,145 mg/l dan 0,077 mg/l. Content of Fe dan Mn after practically already under standardized. Effective of thick caused degradation about contains of Fe and Mn in 60 cm about 95,42% dan 92,39%.